The shape of the nation's wealthiest - Hennig, B; Dorling, D (Wiley, 2014)
The debate about the relevance and impact of the super-rich on society has gained greater currency as evidence continues to grow that the widening gap between the poor and the rich has a negative impact on societies as a hole. In otherwise affluent countries where the richest one per cent owns the most, child poverty is common, school attainment is lower and medium household incomes are depressed. Along with reduced average living standards, housing is of poorer quality, and health suffers as anxiety rises.